2016
DOI: 10.1080/15384047.2016.1177685
|View full text |Cite
|
Sign up to set email alerts
|

Fibersol-2 induces apoptosis ofApc-deficient colorectal Cancer (SW480) cells and decreases polyp formation inApcMIN mice

Abstract: The consumption of dietary fibers has been implicated with a lowered risk of human colorectal cancer. Proposed mechanisms involve alterations in the stool consistency, transit time, and formation of shortchain fatty acid by dietary fiber fermentation, and the reorganization of gut microbiota. Here we show that Fibersol-2, a digest-resistant maltodextrin, not only inhibits proliferation of colorectal SW480 cancer cell lines by increasing reactive oxygen species (ROS), but decreases the numbers of the adenoma co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Resistant maltodextrin (RM), a soluble dietary fiber classified as resistant starch type V, will not be absorbed in the small intestine because of its debranching structure [ 30 ]. A previous study has even indicated anticancer activity of resistant maltodextrin in vitro [ 18 ]. In the present study, we found that RM oral administration could alleviate the DAI score increase induced by DSS, improve the intestinal histology damage, and significantly suppress the proinflammatory cytokines through increasing faecal butyric acid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resistant maltodextrin (RM), a soluble dietary fiber classified as resistant starch type V, will not be absorbed in the small intestine because of its debranching structure [ 30 ]. A previous study has even indicated anticancer activity of resistant maltodextrin in vitro [ 18 ]. In the present study, we found that RM oral administration could alleviate the DAI score increase induced by DSS, improve the intestinal histology damage, and significantly suppress the proinflammatory cytokines through increasing faecal butyric acid.…”
Section: Discussionmentioning
confidence: 99%
“…Resistant maltodextrin (RM), a soluble dietary fiber [ 16 ] classified as resistant starch type V, is produced by debranching of the starch structure [ 17 ]. Fibersol-2 (a type of digest-resistant maltodextrin) showed anticancer activity in vitro [ 18 ] and is fermentable in the colon by colonic bacteria and produces short-chain fatty acid [ 17 ]. Fibersol-2 can also increase faecal Bifidobacterium populations and butyrate proportion [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gu et al found that the citrus peel residue SDF has good antioxidant capacity and can promote intestinal health . Sara et al found that water-soluble dietary fiber Fibersol-2 inhibits the proliferation of colorectal cancer cell SW480 by increasing reactive oxygen species (ROS), while reducing the number of intestinal adenomas in mice …”
Section: Introductionmentioning
confidence: 99%
“…20 Sara et al found that water-soluble dietary fiber Fibersol-2 inhibits the proliferation of colorectal cancer cell SW480 by increasing reactive oxygen species (ROS), while reducing the number of intestinal adenomas in mice. 21 Foxtail millet (Setaria italica L.), an annual grass plant, is widely planted worldwide and is a good source of dietary fiber, vitamins, proteins, minerals, and other nutrients. It has pharmacological properties such as anticancer, anti-inflammatory, antioxidant, hypoglycemic, and intestinal health enhancement.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the prevailing consensus is that short-chain fatty acids, represented by butyrate, were produced by commensal butyrate-producing bacteria in the large intestine [ 12 , 13 , 14 ] through fermentation of non-digestible dietary fibers [ 15 ] like polydextrose (PDX) [ 16 ] and fibersol-2 (FS2) [ 17 ]. Butyrate plays a critical role in maintaining gut epithelial cell homeostasis as their primary energy source, and it could inhibit CRC cells growth and promotes apoptosis by modulating the inhibition of histone deacetylases (HDAC) and NF-kB proinflammatory signaling pathways [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%